Emulsion-Blow Spun Self-Sustained Crystalline β-Silicon Carbide (SiC) Fiber Mat and Its Conductivity Property. Issue 3 (3rd July 2017) - Li, Yafang; Yan, Guilong; Zhao, Yixia; Kang, Weimin; Li, Lei; Zhuang, Xupin; Cheng, Bowen; Li, Xiaojiu
ABSTRACT: Micro-scale silicon carbide (SiC) fiber mat was produced by blowing of an oil-in-water (O/W) precursor emulsion process combined with a thermal curing treatment and a subsequent calcination at high temperature, which we named emulsion-blow spinning (EBS). An air flow with high velocity was used to attenuate the O/W emulsion jets, and the as-spun fibers can be successfully self-sustained to three-dimensional network structure. Polycarbosilane micelles (precursor) entrapped in an aqueous polyoxyethylene matrix resulted in SiC fibers with β crystalline after pyrolysis and ceramic process. The SiC fiber mat was tested with an excellent thermal stability and semi-conductivity, may have potential applications on electronic and energy storage. GRAPHICAL ABSTRACT: